2017
DOI: 10.1177/1010428317694563
|View full text |Cite
|
Sign up to set email alerts
|

Potential prognostic long non-coding RNA identification and their validation in predicting survival of patients with multiple myeloma

Abstract: Multiple myeloma, a typical hematological malignancy, is characterized by malignant proliferation of plasma cells. This study was to identify differently expressed long non-coding RNAs to predict the survival of patients with multiple myeloma efficiently. Gene expressing profiles of diagnosed patients with multiple myeloma, GSE24080 (559 samples) and GSE57317 (55 samples), were downloaded from Gene Expression Omnibus database. After processing, survival-related long non-coding RNAs were identified by Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…In the meanwhile, it can interact with miRNA, protein coding genes, and individual lncRNA to contribute to the progression of various cancers (25,26). Over the years, many types of lncRNAs have also been revealed as a prognostic factor and therapeutic targets in many kinds of cancers (27)(28)(29)(30)(31)(32). The lncRNA XLOC_013703 is 2336 nt in length, located in chr20 (start: 24930648; end: 24932983; − strand), consisting of 2 exons.…”
Section: Discussionmentioning
confidence: 99%
“…In the meanwhile, it can interact with miRNA, protein coding genes, and individual lncRNA to contribute to the progression of various cancers (25,26). Over the years, many types of lncRNAs have also been revealed as a prognostic factor and therapeutic targets in many kinds of cancers (27)(28)(29)(30)(31)(32). The lncRNA XLOC_013703 is 2336 nt in length, located in chr20 (start: 24930648; end: 24932983; − strand), consisting of 2 exons.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that dysregulation of lncRNAs is involved in the genesis and progression of MM (10,11). For instance, overexpression of lncRNA imprinted RNA near maternally expressed 3 promoted the osteogenic differentiation of mesenchymal stem cells from MM patients by targeting the transcription of bone morphogenetic protein 4 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dysregulated expression of lncRNAs has been indicated to be involved in the development and progression of various human cancer types, and these molecules are considered to be promising biomarkers and therapeutic agents for cancer (8,9). Numerous lncRNAs that have been implicated in MM progression and development by functioning as tumor suppressors or oncogenes (10,11). Consequently, understanding the underlying mechanism and biological functions of lncRNAs in MM may provide new approaches for its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), which are long considered “junk RNAs” without biological functions, have been shown to provide considerable essential information for predicting the survival of multiple types of tumors [6-8]. Our previous study identified MM-associated lncRNAs using gene chip technology and bioinformatics databases.…”
Section: Introductionmentioning
confidence: 99%